DETERMINAN STRUKTUR MODAL EMITEN ANGGOTA DAFTAR EFEK SYARIAH - Rizal Ma'ruf Amidy Siregar (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2017)
This study was tried to see the effect of the fundamental financial ratios as internal factors and sharia stock prices as an external factor on the characteristics of the capital structure. Emiten in this research are companies that is always listed in the Jakarta Islamic Index from 2012 through 2014. There are eighteen companies that qualify for the study limitation. The researcher found that the structure of assets (Model 1 and Model 3) and the sharia stock price (Model 2 and Model 3) is always have a negative effect on the capital structure. Thus, the increase in asset structure and sharia stock prices led to a decrease in capital structure, and vice versa. In other words, increasing in those two variables have a stake in the management decision to reduce the proportion of long-term debt, and vice versa. One variable that is always has positive effect is the sales growth.